Sport in Australasian society past and present (Sport in the global society, 2000)
As Sydney prepares to host the 2000 Olympic games, this study assesses the cultural impact of sport on the Australasian countries. Here, as in other parts of the world, sport is taken as an assertion of both individual and group identity, a demonstration of modernity and a source of personal, local and regional esteem. This collection explores the political, social and aesthetic influence of modern sport, attitudes to the body and the evolution of specific Australasian visions of sport.